Impact of a reduced metabolizable protein supply during the transition period on the immune and metabolic status of dairy cows - G. Tapp; P. Lacasse; F. Beaudoin; D.R. Ouellet; F. Malouin; C. Ster (Journal of Dairy Science)
ABSTRACT: During the transition period, the incidence of diseases increases due to a negative energy balance that affects metabolic and immune status. Limiting milk production at the beginning of lactation by milking once a day or by incompletely milking twice a day improves the metabolic and immune status of cows. Previous studies have shown that milk production is highly responsive to additional MP. Therefore, reducing MP intake could provide an alternative strategy. This study evaluated whether reducing the MP supply during the transition period could limit milk yield temporarily and thereby improve the cows' metabolic and immune status. A first group of cows (n = 11, 80% MP) was fed a diet formulated to supply 80% of their MP needs during the treatment period (from 10 d before expected calving to 14 DIM) while they received a diet formulated to supply 100% of their MP needs before treatment (adaptation, d 28 to d 11 before expected calving) and after (follow-up, 15 to 28 DIM) the treatment period. A second group of cows (n = 12, 100% MP) was fed a diet formulated to supply 100% of their MP needs during the 3 periods. Blood samples were taken on average at d 26 ± 3.6; d 19 ± 3.7; d 12 ± 3.6; d 9 ± 3.6 before calving and at 2, 5, 7, 10, 14, 21, and 28 DIM to assess the metabolic and immune status. Milk samples were collected at the same frequency to assess milk composition. The milk production of the 80% MP cows was numerically smaller than that of the 100% MP cows (2.4 kg/d) from d 0 to 14, but not after the MP restriction ended. The 80% MP cows had numerically more plasma BHB during the treatment period than the 100% MP cows (694.6 vs. 574.0 ± 389.8 µM, respectively). The 80% MP cows had significantly less glucose on d 7 and d 10 than the 100% MP cows (3.14 vs. 3.44 ± 0.06 and 3.15 vs. 3.42 ± 0.07 mM, respectively). Throughout the 3 experimental periods, no differences were observed for nonesterified fatty acids or for some of the markers of the mobilization of muscle reserves. However, the concentration in 3-methyl-His was greater for the 80% MP cows during treatment and was not different during the follow-up period. The PMN oxidative burst of the 80% MP cows was numerically greater during treatment and on d 21. The treatment did not alter the proliferation of peripheral blood mononuclear cells or PMN phagocytosis capacity. In conclusion, a 20% reduction in MP supply during the transition period did decrease milk production, but this decrease was not sufficient to improve energy balance and to reduce metabolic and immune disturbances.